Children's Story Book on Science and Social Learning Oriented Pancasila Student Profile - Susanti, Ni Kadek Wina; Suastika, I Nengah (MIMBAR PGSD Undiksha, 2022)
The main characteristics of Pancasila students are not yet fully understood by students. So teaching the values of the Pancasila student profile requires the right way. This study aims to produce a children's storybook oriented to the profile of Pancasila students for fourth-grade students. This type of research is development research and uses a 4-D research model. The subjects in this study were three experts, teachers, and 34 grade 4. Based on the calculation of the practicality test criteria for student responses to story books, the results were 98.5. These results indicate that the storybook meets the very practical criteria. Based on the calculation of the average gain score, the average result is 0.71, meaning that the storybook developed has a high level of effectiveness. The result of the development of this research is a children's storybook oriented to the profile of Pancasila students for chapter 6, Indonesiaku Kaya Budaya Class IV SD/MI, which was developed based on the 4D development model. So, it can be concluded that the storybook developed has a high level of effectiveness and can be used in the learning process. The implications of this research can be used as teaching materials to exemplify and cultivate the values of the Pancasila student profile.